A Dynamic Model of Internally-Driven Corporate Social Responsibility and Enlightened Profit Maximization - Fabio Balboni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The aim of this paper is to contribute to the analysis of Corporate Social Responsibility (CSR) from an economic perspective, in two ways. Firstly, introducing a new definition and a new framework of analysis, which can account for both the externallydriven and the internallydriven view of CSR. Secondly, developing a dynamic model of internallydriven CSR – which draws inspiration from the literature on renewable resources – to show that, under certain circumstances, an enlightened profit-maximizing firm will behave as 'Socially-Responsible' to the eyes of the society. The paper also discusses some possible limits and extensions of this theoretical framework.
Keywords: 330